2021
DOI: 10.4254/wjh.v13.i11.1688
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal liver enzymes: A review for clinicians

Abstract: Liver biochemical tests are some of the most commonly ordered routine tests in the inpatient and outpatient setting, especially with the automatization of testing in this technological era. These tests include aminotransferases, alkaline phosphatase, gamma-glutamyl transferase, bilirubin, albumin, prothrombin time and international normalized ratio (INR). Abnormal liver biochemical tests can be categorized based on the pattern and the magnitude of aminotransferases elevation. Generally, abnormalities in aminot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 43 publications
2
32
0
1
Order By: Relevance
“…Because albumin is synthesized in the liver, it is considered a biomarker for the synthetic function of the liver. However, other factors can affect albumin levels, including systemic inflammation, protein malnutrition, nephropathy, fluid overload, and protein-losing enteropathy (14). Our study showed that the TP and ALB concentrations in viral hepatitis patients were lower than in controls, and it agrees with another study that found a significant decrease (p < 0.05) in the TP and ALB concentrations in viral hepatitis patients (15).…”
Section: Discussionsupporting
confidence: 91%
“…Because albumin is synthesized in the liver, it is considered a biomarker for the synthetic function of the liver. However, other factors can affect albumin levels, including systemic inflammation, protein malnutrition, nephropathy, fluid overload, and protein-losing enteropathy (14). Our study showed that the TP and ALB concentrations in viral hepatitis patients were lower than in controls, and it agrees with another study that found a significant decrease (p < 0.05) in the TP and ALB concentrations in viral hepatitis patients (15).…”
Section: Discussionsupporting
confidence: 91%
“…As for the upregulated DEPs, alkaline phosphatase (ALPL), also named ALP, together with alanine aminotransferase (AST), aspartate aminotransferase (ALT), bilirubin, and albumin is already known as a biochemical indicator for liver function tests. If the serum level of ALP exceeds the normal range of 30–120 IU, it means that liver function is impaired [ 44 ]. Apart from the aforementioned information, ALDOB is enriched in the liver and kidney, as well as the small intestine [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liver enzyme alteration can be found in various liver diseases, but if you look closely, the common causes of liver disease have typical patterns [ 6 , 7 ]. For example, ischemic liver injury shows marked aminotransferase level (>1000 IU/L), and viral hepatitis or toxic hepatitis show slightly lower aminotransferase levels than the above disease.…”
Section: Discussionmentioning
confidence: 99%